The Employment and Earnings Gaps between Natives and Immigrants in the UK between 1981 and 20061. (16th April 2018) - Lemos, Sara
Abstract: We exploit the sizeable and long Lifetime Labour Market Database (LLMDB) to estimate the immigrant–native employment gap across gender, across continents of nationality and across lengths of stay in the UK between 1981 and 2006. These estimates are a novel contribution, as estimates for men and women are scarce in the literature and estimates across immigrants' origins and lengths of stay are as yet unavailable. Furthermore, we estimate the employment gap as the differential in the number of employed weeks in the year between immigrants and natives, which has not been done before – this contrasts with the employment probability gap usually estimated in the literature. We also estimate the immigrant–native earnings gap across gender, across the entire earnings distribution, across continents of nationality and across lengths of stay. Estimates across the earnings distribution are also a novel contribution, as these are also as yet unavailable in the literature. Our main conclusion is that both the immigrant–native employment and earnings gaps vary across gender, continents of nationality and lengths of stay. Immigrant women earn more than native women throughout the distribution. The earnings gap is positive throughout for females: smaller at the bottom, larger at the top and relatively constant in the middle of the distribution. In contrast, it increases monotonically across the distribution for males: it is negative at the bottom and positive at the top. In the main, immigrants from Africa, Asia and the Middle East, Central and South America, and Eastern Europe suffer larger employment and earnings penalties, which are reduced as their length of stay increases. In contrast, immigrants from North America have a more favourable labour market experience.